Climate crossroads: How global warming drives coronavirus emergence, the long COVID crisis of tomorrow, and AI's role in navigating our future - Rudroff, Thorsten (Elsevier Masson, 2025)
This narrative review examines the critical nexus between climate change, coronavirus emergence, and Long COVID-a triad that may shape public health outcomes for generations. Climate change disrupts ecological balances that have historically limited viral spillover events, creating novel interfaces between wildlife reservoirs and human populations. The coronavirus family presents particular concern due to its diversity, adaptability, and demonstrated capacity for cross-species transmission. With over 200 coronaviruses identified in bat populations alone, this vast reservoir of genetic diversity, combined with the family's propensity for recombination, creates substantial pandemic potential that climate disruption may further amplify. Long COVID has revealed another dimension of the coronavirus threat: the potential for significant chronic disease burden following acute infection. This complex multisystem condition affects a substantial portion of SARS-CoV-2 infected individuals, with mechanisms including viral persistence, autoimmunity, microclot formation, and mitochondrial dysfunction. Future projections suggest that climate change could increase global viral spillover risk by 30-45% by 2070, particularly in Southeast Asia, Central Africa, and parts of South America. Artificial intelligence offers promising tools for addressing these interconnected challenges through enhanced surveillance, accelerated therapeutic development, and optimized healthcare delivery. Understanding the climate-coronavirus-chronic illness nexus has become essential to the development of resilient health systems and effective planetary health policies face to an uncertain future.